Plasma column position measurements using magnetic diagnostics in ADITYA-U tokamak. (28th September 2021) - Aich, S; Kumar, R; Macwan, T M; Kumavat, D; Jha, S; Tanna, R L; Sathyanarayana, K; Ghosh, J; Jadeja, K A; Patel, K; Patel, Sharvil; Ranjan, Vaibhav; et al.
Abstract: Due to several forces acting on the plasma column in a tokamak, the plasma column tends to move horizontally and/or vertically leading to many adverse events including termination of plasma. Precise measurement of plasma column position throughout the discharge with good temporal resolution in the real time is hence necessary in order to restrict the column movement using the stabilizing equilibrium magnetic fields. The plasma column position is measured by several magnetic diagnostics such as magnetic pick-up probe, Mirnov coil, Sine-Cosine coil along with flux loops in ADITYA Upgrade tokamak (ADITYA-U). In spite of the simplicity of the measurement principle of these probes as well as of their construction, obtaining the position of the plasma column is not very straightforward. The diversity of all these magnetic diagnostics in terms of their structures, installation location, mounting scenario etc leads to improper position estimations as these probes are being affected differently by the unwanted magnetic pick-ups. These unwanted pickups, especially those arising from vessel eddies, are successfully removed by introducing a scaling method for all the above-mentioned position probes in ADITYA-U based on the in situ calibration of these probes. The correction factors are deduced by estimating the known positions of a central current carrying conductor correctly using the probe measurements during the in situ calibration. These correction factors are used for estimating the plasma column position in the tokamak experiment along with proper nullification of magnetic fields arising from other magnets during tokamak operation. The plasma column position estimation from different magnetic probes are compared with each other and also with those estimated from diagnostics other than the magnetic ones.